Breast cancer microenvironment regulation by food and medicine homology substances - Yimao Wu; Ziling Zeng; Yinting Hu; Zichang Chen; Gokhan Zengin; Huijie Miao; Meng-Yao Li (Food, Nutrition and Health, 2026)
Abstract Breast cancer (BC) represents the primary threat to women’s health worldwide, with its associated disease burden increasing continuously. Although conventional therapies represented by chemotherapy and targeted therapy serve as the cornerstone of current treatment, their accompanying systemic toxic and side effects, as well as insufficient regulation of the tumor microenvironment (TME), have increasingly become bottlenecks restricting the improvement of therapeutic efficacy and patients’ quality of life. Against this background, natural food materials and their active components derived from the traditional Chinese medicine theory of “food and medicine homology” exhibit unique potential in this emerging therapeutic strategy of modulating the TME, owing to their inherent characteristics of low toxicity and multi-target effects. This review aims to systematically elaborate the molecular mechanisms underlying the targeted regulation of the BC TME by active components from food and medicine homologous materials, in an effort to provide novel, safe and prospectively applicable strategies for the adjuvant prevention and treatment of BC.